Hydrothermal indications of Early Cretaceous red beds in lacustrine successions, North Yellow Sea Basin, eastern China. (December 2017) - Wang, Ren; Shi, Wanzhong; Xie, Xiangyang; Wang, Liaoliang; Busbey, Arthur B.; Manger, Walter; Xia, Zhimin
Abstract: Controversies over the origin of globally distributed Cretaceous red beds have mainly focused on climate vs. weathering with potential hydrothermal influence. In comparison to Cretaceous Oceanic Red Beds, Cretaceous lacustrine red beds exhibit chronological inconsistencies and their diverse tectonic settings suggest differing genetic mechanisms. In this paper, Early Cretaceous red beds in the North Yellow Sea Basin, one of Mesozoic rift basins in eastern China that are associated with multi-phase magmatic activities, was chosen to document potential hydrothermal impact. Geological and geochemical analyses show that these red beds were syndepositional products developed in shallow to moderately deep lacustrine environments and that they were influenced by hydrothermal activity. Major and trace elements, including enhanced Al2 O3 -normalized Fe2 O3 and Fe2 O3 (total) values, Al/(Al + Fe + Mn) and (Fe + Mn)/Ti ratios, Ni-Co-Zn and Fe-Mn-(Ni + Co + Cu)*10, ∑REE-La/Yb, the concentrations of hydrothermally-related ions, invalid redox indicators of trace elements, abnormally high Fe2 O3 (total) content, positive Eu anomaly, correlation of Fe2 O3 (total) and Eu anomaly, and vitrinite reflectance (Ro) vs. total organic carbon (TOC), all show strong hydrothermal fluid influence and heating effects. By integrating and comparing data from previous studies, we propose a hydrothermally affected sedimentation model for Cretaceous red beds and associated sediments in magma-activated lacustrine basins, and conclude that the enriched metallic ions introduced by the hydrothermal fluids may be the most significant reason for the deposition of the red beds, and the flushed ferric ions, accompanied by hydrothermal fluid, are the main ions that are hosted inside hematite causing the red sediment. This model can be applied to similar lacustrine basins that experience strong magmatic activity. Highlights: Cretaceous red beds were syndepositional products developed in subaqueous. Cretaceous red beds in lacustrine strata were affected by hydrothermal activities. Hydrothermal fluids offered enriched iron ions and caused red sediment. Magma invaded along the surrounding layers and affected the normal sedimentation.